City Heritage Tourism without Heirs - Olivia Sandri (Cybergeo)
Throughout Europe products of Jewish culture – or what is perceived as such – have become viable components of the popular public domain. Jewish-themed tourism has emerged since the 1990s in a number of European cities after decades of “collective amnesia”, and some of the Jewish areas have recently undergone a ‘Jewish-thematisation’.The focal point of this article is the usage of heritage in former Jewish areas. The aim is to understand in which ways and to what extent Jewish heritage is used for tourism purposes. A comparison between Krakow and Vilnius underlines what this difference in usage depends on, in the context of increasingly popular cultural and heritage tourism. In order to understand how Jewish-themed tourism has developed an inventory of Jewish heritage and Jewish-themed events in the two cities is made, showing that Jewish heritage is mainly used for economic development through tourism as well as commemoration in Krakow, whereas in Vilnius, it is used for commemoration and for the needs of the local (Jewish) community. The complexity of the topic and the importance of various local factors in the usage of Jewish heritage are shown. There does not exist, neither in Krakow nor in Vilnius, any specific public policies regarding Jewish heritage that can explain the ’degree’ of touristification and ’heritagisation’ of the areas. Furthermore, a range of connected theoretical issues, such as authenticity, commodification of culture, or ownership of heritage, is raised.